Transcription immunoassay: light-up RNA aptamer-based immunoassay using in vitro transcription. Issue 25 (8th March 2019) - Sim, Jieun; Byun, Ju-Young; Shin, Yong-Beom
Abstract : Here, we first report an ultra-enhanced immunoassay for sensitive and reliable biomarker detection using layer-by-layer assembly and transcription-assisted light-up aptamer generation to induce signal amplification. Abstract : Here, we present an ultra-enhanced immunoassay for sensitive and reliable biomarker detection using layer-by-layer assembly and transcription-assisted light-up aptamer generation to induce signal amplification. This dendrimer structure-based transcription immunoassay is ∼1500 times more sensitive than commercial fluorescence ELISA, achieving a detection limit of 108 aM.